The Influence of Photocatalytic Reactors Design and Operating Parameters on the Wastewater Organic Pollutants Removal—A Mini-Review - Enesca, Alexandru (Catalysts, 2021)
The organic pollutants removal by conventional methods (adsorption, coagulation, fil tration, microorganism and enzymes) showed important limitation due to the reluctance of these molecules. An alternative to this issue is represented by the photocatalytic technology considered as an advanced oxidation process (AOP). The photoreactors design and concepts vary based on the working regime (static or dynamic), photocatalyst morphology (powders or bulk) and volume. This mini-review aims to provide specific guidelines on the correlations between the photoreactor concept characteristics (working regime, volume and flow rate), irradiation scenarios (light spectra, irradiation period and intensity) and the photocatalytic process parameters (photocatalyst materials and dosage, pollutant type and concentration, pollutant removal efficiency and constant rate). The paper considers two main photoreactor geometries (cylindrical and rectangular) and analyses the influence of parameters optimization on the overall photocatalytic efficiency. Based on the systematic evaluation of the input data reported in the scientific papers, several perspectives regarding the photocatalytic reactors’ optimization were included.
Keywords: reactors; flow rate; photocatalysts; light radiation; organic pollutants